(untitled) (Latakia University Journal -Basic Sciences Series, 2018)
تم في هذا البحث دراسة التأثيرات المتبادلة بين CdCl2 و MgCl2 في وسط المحل العضوي دي اتيل أمين (Et2NH) ترافقت هذه التأثيرات بارتفاع درجة حرارة المزيج في الجملة المدروسة ، وإنتباج الطور الصلب لفترة من الزمن . ودراسة التوازنات الطورية وشروط تشكل المركبات في الجملة التالية : CdCl2 - MgCl2-Et2NH T=25C° , T=50C° وفقاً للتفاعل التالي : aCdCl2+bMgCl2+nEt2NH ® aCdCl2.bMgCl2.nEt2NH ودرست أيضاً الشروط اللازمة لفصل المركبات المعقدة المتشكلة عن جملها . ودراسة بعض خواصها الفيزيائية والكيميائية بواسطة : (IR-Spectroscopy ) و (UV-Spectroscopy ) أظهرت هذه الدراسة أن التأثيرات المتبادلة بين CdCl2 و MgCl2 في المحل العضوي Et2NH حدثت في الشروط العادية من درجة حرارة وسرعة تحريك دوراني وزمن ، وتشكلت مركبات متعددة الأمينات لكلوريد الكادميوم والمغنزيوم مع وجود روابط تساندية M-N حيث M=Cd,Mg ، وجسور كلورية أظهرتها الدراسة الطيفية للمركبات. The interactions between CdCl2 and MgCl2 in the medium of the organic solvent Di-ethyle Amine (Et2NH) were studied . These effects were accompanied by elevation of the temperature of the mixture in the system under study, and swelling of the hard phase for a while . Also were studied the phasic balances , and the formation conditions of compounds in the following system : CdCl2 - MgCl2-Et2NH T=25C° , T=50C° According to the following reaction : aCdCl2+bMgCl2+nEt2N ® aCdCl2.bMgCl2.nEt2NH The conditions required for separating the compounds formed in their systems, in addition to some physical and chemical characteristics of these compounds were studied by ( UV-Spectroscopy) and ( IR-Spectroscopy ( . This Study revealed that the interaction between CdCl2 and MgCl2 in the organic solvent Et2NH , took place in normal conditions , as concerns temperature, speed of the circular movement and time . The poly amine compounds of the cadmium chloride and Magnesium chloride were formed with coordinate bonds M-N where M=Cd, Mg and chloride bridges revealed by the spectral study of the compounds.